MANAJEMEN LABA TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE GOVERNANCE SEBAGAI PEMODERASI - Herman Darwis (Jurnal Keuangan dan Perbankan, 2012)
The objective of study was to provide empirical evidence of the influence of earnings management on corporatevalue. Managerial ownership affected the relationship between earning management with corporate values,and institutional ownership affected the relations between earning management to the corporate value.Thepopulation of this study was manufacturing companies listed on the Indonesia Stock Exchange, the observa-tion period from the year 2008-2010. The technique used was purposive sample with the analysis method usedwas a simple regression for hypothesis one, and moderate analyst regression for hypotheses two and three. Thestudy found that earnings management had no effect on corporate value. Managerial ownership did not affectthe relationship between earnings management to corporate value. Institutional ownership affected the rela-tionship between earnings management to corporate value. Ownership of shares held by institutional partiescould weaken the influence of earnings management on corporate value. It was because the institutional own-ership could control the company more closely so that the possibility of management performed earningsmanagement could be reduced.